Agroecological planning of productive systems with functional connectivity to the ecological landscape matrix: two Colombian case studies - Acevedo-Osorio, Álvaro; Cárdenas, Jonathan Salas; Martín-Pérez, Angela Maribeth (Frontiers in Sustainable Food Systems, 2024)
Given the need for agricultural system management under sustainability principles, identification and quantification of the landscape structure surrounding production systems is a tool that allows farmers to make their agroecological transition processes more appropriate. An ACI with eight indicators was proposed for farm assessment. This ACI is focused on functional connectivity both at farm and landscape levels. Two Colombian farms with different connectivity characteristics were evaluated under the index. Tosoly presented a stronger ecological structure and higher connectivity and diversity. Villa Alicia showed a weak ecological structure and low connectivity and complexity. From a systemic approach, the ACI allows an analysis of landscape structural conditions that promote ecological functions of pollination and biological controllers. With landscape structural conditions, it is possible to analyze the quantity and quality of the habitat for designing agroecological transition programs focused on obtaining productive agroecosystems that simultaneously comply with conservation strategies.